Increasing Local Government E-Government Innovation in Achieve Good Government - Raja Kamsyah Bangun; Rahmanta Rahmanta; Satia Negara Lubis (Budapest International Research and Critics University, 2022)
The aims of this study to find out the Increasing Local Government E-Government Innovation in Achieve Good Government. This study uses qualitative research Method. The result of this study shows that the procedure for granting People's Business Credit (KUR) by Bank Mandiri KCP Medan Brahrang in the process of distributing bank KUR using an internal and or external scoring system to assess, analyze and record a credit application process until an account is formed. As well as the analysis process and referring to the applicable Credit Standard Procedures (SPK) and or Operational Technical Guidelines (PTO). And the authority to decide on KUR credit refers to the provisions of the Standard Credit Procedures (SPK) applicable at the Bank. People's Business Credit (KUR)(X1) has a positive and significant effect on the production of oil palm farming in Langkat Regency with a probability value of 0.00. Land area (X2) has a positive and significant effect on oil palm farming production in Langkat Regency with a probability value of 0.03. Fertilizer (X3) has a positive and significant effect on oil palm farming production in Langkat Regency with a probability value of 0.00, and Pesticide (X4) has a positive and insignificant effect on oil palm farming production in Langkat Regency with a probability value of 0.11.